Effective Test Administration in Schools: Principles and Good Practices for Test Administrators - Aloysius Rukundo; Justine Magambo (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
To establish academic achievement in any public school, teachers have to construct, administer and score tests or examinations. For a valid and reliable assessment of academic achievement, the tests should yield similar and consistent results/grades for comparable groups of students. The validity and reliability of assessment are dependent on many factors among which are administrations of the measurement. This paper focuses on test administration principles and good practices in schools; highlighting principles and good test administration practices and concluding with a summary of the suggestions that, if followed, lead to successful test administration in a any given public school system.